Identifikasi Alih Fungsi Lahan Pertanian dan Kondisi Sosial Ekonomi Masyarakat Daerah Pinggiran di Kecamatan Gunungpati Kota Semarang - Nurma Kumala Dewi; Iwan Rudiarto (Department of Urban and Regional Planning, Diponegoro University, 2013)
The increasing and the development society of Semarang city which aim to the suburb of Semarang (peri-urban area) give occasion to land needs in the edge area has increased. Sub-district Gunungpati is one of suburb which consists of the area of peri-urban of Semarang city goes to the area of development of Semarang city. The land conversion specifically of agriculture causes the change of social economic condition of society. It is possible to change the means of livelihood of the society from farmer going to non-farmer, or even going to jobless. If it runs continuously, it may threaten the persistence of peri-urban society livelihood specifically the farmer itself. Therefore, the purpose of the study is to identify the development of agriculture land conversion being the non-agriculture (built up area) and to analysis socio-economics condition of society relate to agriculture land conversion. Based on the result of the study, the agriculture land conversion is happened progressively on areas development such as the area of city center nearby, education area and corridor which goes to the entrance to sub-district Gunungpati. The wide land conversion of the agricultural area has became constructed area in the subdistrict over 16 years (1994-2010) for rice fields around 384.40 ha, and for dry fields around 414.41 ha. The agriculture land conversion has changed the social economic condition of society. The farmers who lose their rice field have decreased income. It is caused by the level of education and skills of them are still low, so that way, they cannot access formal job. Besides that, because the lose of agriculture area, now they are looking for their economy differently. The existence of different economic activity, and the entry of new comer in their area create the relationship between them are faded.